Cut-off point estimation of Neck circumference to determine Overweight and Obesity among Asian Indian adults (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Neck circumference (NC) is a relatively new anthropometric measure of differentiating body fat distribution and considered as a marker of upper subcutaneous adiposity.Aims and Objectives: The present study was undertaken to assess the suitability and cut-offs estimation of NC to determine overweight and obesity in Asian Indian adults.Materials and Methods: The present cross-sectional study was carried out among 1830 adults (914 males; 916 females) aged 20-49 years of Karbi-Anglong, Northeast-India, using multistage-stratified sampling method. Height, weight, waist circumference (WC) and neck circumference (NC) were recorded using standard procedures. The body mass index (BMI kg m−2) was calculated and overweight and obesity were assessed using standard cut-offs. Results: Linear and binary logistic regression analyses showed that NC had a better predictive value of BMI (p